Global health care infrastructure and Africa in times of Covid-19: Insights for sustainable development and future pandemics - Samba Diop; Simplice Asongu (African Governance and Development Institute (AGDI), 2020)
This exploratory study aims to assess Africa's lagging position in global heath in relation to some health care infrastructure before critically examining the situation of Africa in the light of pressing Covid-19 healthcare infrastructural needs in terms of number of hospital beds, intensive care units (ICU) beds and ventilators per 100 000 people. A comparative analysis is provided to showcase which regions are leading in the health facilities in the world in general and Africa in particular as well as countries that are lagging in the attendant healthcare facilities. Analytical insights are provided to illustrate that the Covid-19 pandemic has revealed how Africa cannot reach most Sustainable Development Goals (SDGs), especially SDG-3 on health and wellbeing. Moreover, corresponding inferences suggest that the continent is unprepared for future pandemics in terms of health facilities.
Keywords: E10; E12; E20; E23; I10; I18; 330; Novel coronavirus; Socio-economic effects; Africa